The oxygen uptake response of sprint- vs. endurance-trained runners to severe intensity running - Draper, S. B.; Wood, D. M. (Journal of Science and Medicine in Sport, 2005)
We compared the oxygen uptake (VO2) response of sprint- and endurance-trained runners for an exhaustive square wave run lasting approximately 2 minutes. Six sprinters and six middle- and long-distance runners each performed two exhaustive square wave runs lasting approximately 2 min and two exhaustive ramp tests. VO2 was determined breath-by-breath (QP9000; Morgan Medical, Rainham, UK) and averaged across the two repeats of each test; for the square wave test, the averaged VO2 response (excluding the first 15 s) was then modelled using a monoexponential function. Both VO2peak for the ramp test (67.5+/-3.3 vs. 54.5+/-8.5 mlxkg(-1)xmin(-1); P= 0.006) and the asymptotic VO2 for the square wave run (59.6+/-2.7 vs. 50.7+/-4.6 mlxkg(-1)xmin(-1); P= 0.002) were higher for the endurance than for the sprint group. However, as a percentage of VO2peak, this asymptotic VO2 did not differ between the groups (90.1+/-3.2% (endurance) vs. 96.2+/-9.0% (sprint); P= 0.145). Across all 12 subjects, the %VO2peak attained in the square wave run was negatively correlated with VO2peak (Pearson's r= -0.811, P= 0.001). We conclude that VO2max is more important than training history as a determinant of the %VO2max attained in exhaustive square wave running lasting approximately 2 min.